Toxicology of the kidney - Lash, Lawrence (Henry Stewart Talks, 2009)
Renal structure and functions, Renal blood flow, Renal concentrating and transport mechanisms, Role of kidneys in fluid balance, In vivo assessment of renal function, In vitro models to study kidney toxicology, Classification of nephrotoxic injury, Mechanisms of renal cell injury
Updated at 2015/04/30